Revision of the western Atlantic members of the Alpheus armillatus H. Milne Edwards, 1837 species complex (Decapoda, Alpheidae), with description of seven new species - Anker, Arthur (Zootaxa, 2012)
The western Atlantic members of the Alpheus armillatus H. Milne Edwards, 1837 species complex, which includes someof the largest and most common intertidal snapping shrimps, are revised based on extensive fresh material collected in theCaribbean Sea, Florida, Gulf of Mexico, Brazil, as well as some older museum material. Alpheus armillatus (sensu H.Milne Edwards 1837 and Coutière 1899) is redescribed based primarily on the Caribbean material and a neotype fromAruba is designated. Alpheus lancirostris Rankin, 1900 and A. verrilli (Schmitt, 1924) are resurrected from the synonymyof A. armillatus and rediagnosed. Alpheus angulosus McClure, 2002 is redefined and reported from several new localities;its presence in Brazil is confirmed. Seven species are described as new: A. amarillo sp. nov. (Caribbean, southern Florida,Gulf of Mexico), A. punctatus sp. nov. (Caribbean, southern Florida), A. tampensis sp. nov. (western Florida), A. carlaesp. nov. (Caribbean, Florida, Brazil), A. mathewsae sp. nov. (Caribbean, Florida), A. brasileiro sp. nov. (Brazil), and A.nuno sp. nov. (Mexico). In addition, A. viridari (Armstrong, 1949), a close relative and presumed sister lineage of the A.armillatus complex, is rediagnosed and its distinguishing features are highlighted. All species are abundantly illustrated,including variation of some morphological features and colour patterns. A character table and a key to the western Atlantic species of the A. armillatus complex are provided.